Membrane topology analysis of Escherichia coli K-12 Mtr permease by alkaline phosphatase and beta-galactosidase fusions. - Sarsero, J P (1995)
The mtr gene of Escherichia coli K-12 encodes an inner membrane protein which is responsible for the active transport of trypotophan into the cell. It has been proposed that the Mtr permease has a novel structure consisting of 11 hydrophobic transmembrane spans, with a cytoplasmically disposed amino terminus and a carboxyl terminus located in the periplasmic space (J.P. Sarsero, P. J. Wookey, P. Gollnick, C. Yanofsky, and A.J. Pittard, J. Bacteriol. 173:3231-3234, 1991). The validity of this model was examined by the construction of fusion proteins between the Mtr permease and alkaline phosphatase or beta-galactosidase. In addition to the conventional methods, in which the reporter enzyme replaces a carboxyl-terminal portion of the membrane protein, the recently developed alkaline phosphatase sandwich fusion technique was utilized, in which alkaline phosphatase is inserted into an otherwise intact membrane protein. A cluster of alkaline phosphatase fusions to the carboxyl-terminal end of the Mtr permease exhibited high levels of alkaline phosphatase activity, giving support to the proposition of a periplasmically located carboxyl terminus. The majority of fusion proteins produced enzymatic activities which were in agreement with the positions of the fusion sites on the proposed topological model of the permease. The synthesis of a small cluster of hybrid proteins, whose enzymatic activity did not agree with the location of their fusion sites within putative transmembrane span VIII or the preceding periplasmic loop, was not detected by immunological techniques and did not necessitate modification of the proposed model in this region. Slight alterations may need to be made in the positioning of the carboxyl-terminal end of transmembrane span X.